(untitled) (Agro Productividad, 2025)
Objective: To characterize forb and browse species associated with cattle pastures under the Voisin grazing system. Design/Methodology/Approach: Floristic inventories were conducted at four distinct sites: a weed-dominated pasture (WeedDom), a secondary vegetation pasture (SecVeg), a pasture invaded by weeds (WeedInv), and a fallow field with woody vegetation (W oodVeg). The phenological transition phase was recorded and the growth stage identified for the most abundant species in each paddock. Cattle foraging behavior was assessed using scan sampling of 10 cows during active grazing. Chemical analyses were performed on 18 forage species from all sites to determine crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), lignin, total phenolics, and tannins. Results: A total of 65 species were identified in WeedDom, dominated by Sida spinosa L.; 51 species in WoodVeg, dominated by Solanum adscendens Sendtn.; 51 species in SecVeg, dominated by Cleome viscosa L.; and 57 species in WeedInv, with Andropogon gayanus (Kunth) as the dominant species. Most plants were in vegetative or early blooming stages during the transition phase. Cattle diets were diverse; S. spinosa, Trianthema portulacastrum L., Gomphrena globosa L., Lagascea mollis Cav., and A. gayanus were among the most preferred species. Crude protein content ranged from 5.8% to 20.3%, NDF from 31.5% to 72.9%, and ADF from 21.0% to 40.0%, with lignin levels reaching up to 29.4%. Forage species also contained phenolic compounds (1.28–14.48%) and tannins (1.15–13.78%). Limitations/Implications: This was an exploratory study. Findings/Conclusions: Most forbs and browse species associated with grazing areas across varying growth stages and exhibiting diverse nutrient and phenolic profiles were effectively utilized as forage by cattle under the Voisin grazing system.